Analisis Kualitas Pelayanan untuk Meningkatkan Nasabah Prioritas pada PT. Bank Sumut Syariah Kcp Marelan Raya Medan - Suci Putri Pratiwi; Siti Kadariah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the quality of service to increase priority customers at PT. Bank Sumut Syariah KCP Marelan Raya and to determine the implementation of service quality to increase priority customers at PT. Bank Sumut Syariah KCP Marelan Raya. This study is qualitative with a descriptive approach. The type of data is qualitative data with primary data sources, namely interviews with certain parties, as well as secondary data obtained by researchers from the first source. The methods used in this study are interview methods, observation, documentation, and literature studies. The results of this study are the implementation of the quality of customer service of a bank, of course, encountering many services or conveniences provided by the bank when visiting or requiring administrative matters, these various methods are intended so that the matters owned by customers can be completed, and customers feel satisfied. Providing the best service to every customer owned must be a priority of the banking business. This can provide comfort to customers who come, so that their loyalty continues to increase. Improving the quality of service in general can be done in various ways, which can also be adjusted to the main values ​​of the banking business provided. The implementation of service quality is not only that which is directly provided when customers come to the branch office, but also on other channels when customers come into contact with banking services.